What is the solution of -2a plus 3a plus 5b
3a + 5b - 6a - 9b = -3a - 4b
It is an expression that can be simplified to: 3a-2b+c
Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?
add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b
24am - 9an + 40bm - 15bn = 3a*(8m - 3n) + 5b*(8m - 3n) = (3a + 5b)*(8m - 3n)
15a - 25b + 20 = 5 (3a - 5b + 4)
3a - 2b
It is: 5(3a+b) when factored
5(3a - 5b + 4)
ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.